Legal Protection of Children as Persons of Criminal Abuse in the Investigation Process at Polres Aceh Tenggara - Indra Gunawan Purba; Ervina Sari Sipahutar; Erikson Napitupulu (Budapest International Research and Critics University, 2023)
Children as perpetrators of crimes will also experience a legal process that is identical to adults who commit crimes, the meaning of the word identical here means